2011
DOI: 10.1123/jpah.8.2.210
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Social Support, Perceived Barriers, and Negative Meanings of Physical Activity on Physical Activity in Middle School Students

Abstract: Background:A profound decline in physical activity occurs in puberty. This phenomenon is not well understood. Therefore, the purpose of this study is to examine associations between family/friend social support for physical activity, negative meanings of physical activity (NMPA), and internal /external barriers to physical activity with moderate to vigorous physical activity (MVPA), and sedentary and light behavior (SLB) in youth.Methods:A total of 350 participants from 7 Los Angeles County middle schools part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 57 publications
6
36
0
1
Order By: Relevance
“…There is a lack of studies taking into account support from teachers when investigating the relative importance of family, friends, and teachers on adolescent boys' school-based physical activity. Consistent with the study by Hsu et al [33], the present study identified family support as significantly influencing boys' physical activity, while the effect of friend support was not significant. This finding was explicable based on the substantial reliance of adolescent boys on instrumental or informational and emotional support from family.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There is a lack of studies taking into account support from teachers when investigating the relative importance of family, friends, and teachers on adolescent boys' school-based physical activity. Consistent with the study by Hsu et al [33], the present study identified family support as significantly influencing boys' physical activity, while the effect of friend support was not significant. This finding was explicable based on the substantial reliance of adolescent boys on instrumental or informational and emotional support from family.…”
Section: Discussionsupporting
confidence: 91%
“…Much attention has been paid to comparing the influences of family and friends as sources of social support for adolescent physical activity [11,[29][30][31][32][33]. However, conflicting results were found in previous studies [11,29,30,32,33]. There is a lack of studies taking into account support from teachers when investigating the relative importance of family, friends, and teachers on adolescent boys' school-based physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…contribute to the accumulation of validity evidence for the more general classification of perceived barriers into internal and external factors (21). Finally, the findings showed evidence of subscale score reliability, and thus show promise for researchers using this self-report PB-MVPA scale to understand which types of perceived barriers hinder MVPA.…”
Section: Discussionmentioning
confidence: 68%
“…Others have categorized barriers into two categories representing individual and environmental dimensions (35) or representing negative personal emotions and personal sense of immobilization (33). Investigators have also categorized perceived barriers into either internal or external dimensions (3,12,21). In this case, perceived internal barriers encompass a variety of inner emotions and thoughts that people identify as reasons that interfere with their physical activity participation.…”
Section: Introductionmentioning
confidence: 99%
“…From the social ecological perspective, physical activity behavior is determined by an interaction of multilevel influences across personal, social and environmental factors, although previous studies mainly examine psychological and/or social environmental factors [6][7][8][9][10][11][12]. Few studies have examined physical environmental influences on physical activity, which are recognized as having long-term effects on population-based health behaviors.…”
Section: Introductionmentioning
confidence: 99%